(untitled) (Orfeu, 2024)
The text presents an analysis of the curricular creation logics for the formation of professional popular musicians: Bituca’s proposal (a Brazilian Popular Music University), which presents itself as an alternative to curricula structured by Western classical music – especially those in Higher Education. The following sources were used to gather data: documents produced by the school, semi-structured interviews with coordinators and instructors, and responses from Bituca alumni to an online questionnaire. The theoretical tools of the Legitimation Code Theory allowed both the unveiling of the organizational principles of the curriculum and the understanding of the criticisms directed towards higher music education courses. The results show that Bituca’s curricular creation logic seeks to structure a process of cultivating the popular musician through immersion in practice, promoting interaction with renowned masters in full professional activity and with an intentionally selected repertoire: Brazilian popular music. The knowledge selection is flexible, based on the demands of musical practice and the students.